2020
DOI: 10.18632/oncotarget.27678
|View full text |Cite
|
Sign up to set email alerts
|

Ewing sarcoma family of tumors-derived small extracellular vesicle proteomics identify potential clinical biomarkers

Abstract: Purpose: Ewing Sarcoma Family of Tumors (ESFT), the second most common pediatric osseous malignancy, are characterized by the pathognomonic chromosomal EWS-ETS translocation. Outside of tumor biopsy, no clinically relevant ESFT biomarkers exist. Additionally, tumor burden assessment at diagnosis, monitoring of disease responsiveness to therapy, and detection of disease recurrence are limited to radiographic imaging. To identify new, clinically relevant biomarkers we evaluated the proteome of a subset of ESFT-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 73 publications
(85 reference statements)
0
26
0
Order By: Relevance
“…Small EVs range from 40-160 nm in size and include exosomes (originating from multivesicular endosome compartments) and heterogeneous populations of plasma membrane-derived microvesicles [13]. EVs are secreted by healthy tissue cells as well as by tumor cells, including EwS [14][15][16]. The EV cargo is protected by a lipid membrane and reflects the physiological or pathological state of the parental cell.…”
Section: Introductionmentioning
confidence: 99%
“…Small EVs range from 40-160 nm in size and include exosomes (originating from multivesicular endosome compartments) and heterogeneous populations of plasma membrane-derived microvesicles [13]. EVs are secreted by healthy tissue cells as well as by tumor cells, including EwS [14][15][16]. The EV cargo is protected by a lipid membrane and reflects the physiological or pathological state of the parental cell.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several pieces of evidence of the diversity of transcripts present in EwS EVs, the proteomic content of EwS EVs is only starting to be unraveled. Samuel et al (2020) found that CD99, HINT1, and NGFR can act as biomarkers of small EVs derived from EwS cells. Sorting small EVs derived from EwS cells based on the above protein markers could improve the specificity of EVs derived from heterogeneous cell populations.…”
Section: Clinical Applications Of Ewing Sarcoma Extracellular Vesiclesmentioning
confidence: 89%
“…The most recent study in 2020 by Samuel et al evaluated the effect of 619 proteins composing the subset of ES derived small extracellular vesicles as biomarkers in monitoring the tumor burden at diagnosis, responsiveness to therapy and recurrence [24]. The CD99/MIC2 and the NGFR membrane proteins were chosen to develop a liquid-based assay in order to detect the mRNA cargo of well-established transcripts in ES, such as the EWS-ETS.…”
Section: Ewing Sarcoma (Es)mentioning
confidence: 99%
“…The CD99/MIC2 and the NGFR membrane proteins were chosen to develop a liquid-based assay in order to detect the mRNA cargo of well-established transcripts in ES, such as the EWS-ETS. The liquid biopsy from ES pediatric patients with localized or metastatic disease showed/revealed that the identification of novel extracellular vesicle proteomics has significant diagnostic value [AUC = 0.92, p value = 0.001 for vesicles numeration, with a Positive predictive value = 1.00, 95% CI = (0.63, 1.00) and a Negative predictive value = 0.67, 95% CI = (0.30, 0.93)] compared with tumor-free donors [24].…”
Section: Ewing Sarcoma (Es)mentioning
confidence: 99%